“Frequent fl- erm traveler” – La reformulation euphémistique dans le discours sur l’événement - Charlotte Danino (Lexis: Journal in English Lexicology)
This study deals with the first half hour of CNN’s live broadcast on September 11, 2001. During these 30 minutes, it becomes clear that this is no accident and the events start being considered as we understand them nowadays. This polyphonic stretch of interaction constitutes an online linguistic and discursive construction of a major event, different from, and bigger than, any other before. If we could expect the discourse to alternate between euphemistic and hyperbolic features, the corpus is in fact strikingly neutral. In this context, we propose to study in details a particular case of rephrasing: the set phrase frequent flyer becomes frequent traveler and we hope to show that this is an example of euphemism. We will then try to show how this particular instance finds its roots in phenomena featured in the entire corpus. Indeed, in this rephrasing, three larger means of understatement converge, which we will detail. This will bring us to focus on the particular type of enunciation at stake in our corpus since we will argue that euphemism is an enunciative device applied to the corpus entirely. The apparent neutrality can then be reinterpreted as a general understatement. This will lead us to tackle the implicit aspect of euphemistic discourse: it can mean to not say something or to avoid certain words. Silence, we will argue, is part and parcel of euphemistic discourse. In the context of a stretch of interaction dealing with a (shocking) event, euphemism can be understood as a discursive and enunciative attitude affecting the entire stretch of talk. In the end, we want to consider the relationships between language, cognition and representation in the light of comprehensive euphemistic devices. The unique corpus we study allows us to tackle just that, taking full advantage of the almost simultaneity between what is perceived, focused on and expressed in language.